Meningkatkan Minat dan Kreativitas Mahasiswa untuk Berwirausaha - Ni Made Shinta Adhella (Journal Science Innovation and Technology (SINTECH), 2021)
This paper aims to determine the interests and preferences of students in conducting entrepreneurial activities. In this paper, the data collection technique uses an online questionnaire which is distributed to students in Central Java and Yogyakarta and Medan with various samples of the majors used, namely as many as 45 students. The students who preferred to have their own business and started their business from when they were still students were 97.8%, so this shows that students are very interested in having their own business. 40% chose to have an online business and 24.4% chose another. This shows that students now have the creativity to have a business that is different from the others.